The brooding behavior and physiological differences of Wanxi white geese in different stages of the brooding period - Lei Yang; Caiyun Zhang; Jianwen Cao; Guangpei Xu (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2025)
ABSTRACT In this study, a total of 115 geese were selected and raised in 23 separate pens. We found that the average frequency of brooding was 2.18 times during the whole reproduction period. The duration of broodiness of early, middle, and later stage of the brooding period were 2.96 d, 9.93 d, and 4.27 d, respectively. The daily brooding time of early, middle, and later stage of the brooding period were 13.59 h/day, 21.62 h/day, and 5.26 h/day, respectively. The egg production was negatively correlated with the duration of broodiness in early, middle, and later stage of the brooding period and the daily brooding time of early and middle stage of the brooding period. In addition, the LH, FSH, E2, and P4 levels of laying stage were significantly higher than that of early, middle, and later brooding stage. The E2 level of middle stage was significantly lower than early and later stages. Taken together, we demonstrated that annual egg production of geese can be increased through waking up the brooding geese in the early or middle stage of brooding period. And E2 may be a marker hormone for laying stage of Wanxi white geese.